1999
DOI: 10.1016/s0735-1097(99)00113-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the National Registry of Myocardial Infarction 2 with the Cooperative Cardiovascular Project

Abstract: We conclude that the simpler case ascertainment and data collection strategies employed by NRMI 2 result in process and outcome measures that are comparable to the more rigorous methods utilized by the CCP. Outcomes that are more difficult to measure from retrospective chart review such as stroke and recurrent myocardial infarction must be interpreted cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(50 citation statements)
references
References 21 publications
0
47
0
3
Order By: Relevance
“…The USA Second National Registry of Myocardial Infarction (1994 to 1998) reported a 19.7% mortality; when the analysis excluded cases that were transferred from or to other hospitals, the mortality fell to 13.6%. 17 A multicentric Norwegian study showed a mortality of 18% in 1999; 9 a multicentric Irish study found 18% in the period 1992-1994; 10 the multicentric English study in Nottingham, 21.7% in 1992. 11 Among the Brazilian studies of non-selected cases, there are two that use AIH, describing a mortality of 17.1% in the state of São Paulo in 1997 16 and 18.4% in the state of Rio de Janeiro in 1995.…”
Section: Discussionmentioning
confidence: 99%
“…The USA Second National Registry of Myocardial Infarction (1994 to 1998) reported a 19.7% mortality; when the analysis excluded cases that were transferred from or to other hospitals, the mortality fell to 13.6%. 17 A multicentric Norwegian study showed a mortality of 18% in 1999; 9 a multicentric Irish study found 18% in the period 1992-1994; 10 the multicentric English study in Nottingham, 21.7% in 1992. 11 Among the Brazilian studies of non-selected cases, there are two that use AIH, describing a mortality of 17.1% in the state of São Paulo in 1997 16 and 18.4% in the state of Rio de Janeiro in 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Though this database is large and has been found to be reasonably generalizable (19), there are limitations. First, more than half of the patients who received fibrinolytic therapy were subsequently transferred to another hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Trained abstractors collected detailed data from the hospital records of 772 586 patients from June 1994 to March 1998 at 1674 participating hospitals. Characteristics of the NRMI's data gathering procedures 12 and reliability 13 have been described previously. Using a hierarchical exclusion design, we excluded the following patients (57.4% in total): those transferred into a registry hospital from another facility (171 080; 22.1%); those who presented Ͼ6 hours from symptom onset to hospital arrival (263 343; 34.1%); those whose mode of transport was either unknown or involved transport by air (3941; 0.5%); those who were in cardiogenic shock, because these patients would not likely be able to arrive via self-transport (5340; 0.7%); and those who developed MI Ͼ24 hours after initial hospitalization.…”
Section: National Registry and Study Populationmentioning
confidence: 99%
“…The definitions of the remaining variables are described elsewhere. 12,13 There were few variables that were missing in excess of 5%, and they included time intervals from symptom onset to hospital arrival and from hospital arrival to initial ECG (10%).…”
Section: Study Variables and Definitionsmentioning
confidence: 99%